Starvation at the larval stage increases the vector competence of Aedes aegypti females for Zika virus. - Christie S Herd; DeAna G Grant; Jingyi Lin; Alexander W E Franz (Public Library of Science (PLoS), 2021)
Aedes aegypti is the primary vector of Zika virus (ZIKV), a flavivirus which typically presents itself as febrile-like symptoms in humans but can also cause neurological and pregnancy complications. The transmission cycle of mosquito-borne arboviruses such as ZIKV requires that various key tissues in the female mosquito get productively infected with the virus before the mosquito can transmit the virus to another vertebrate host. Following ingestion of a viremic blood-meal from a vertebrate, ZIKV initially infects the midgut epithelium before exiting the midgut after blood-meal digestion to disseminate to secondary tissues including the salivary glands. Here we investigated whether smaller Ae. aegypti females resulting from food deprivation as larvae exhibited an altered vector competence for blood-meal acquired ZIKV relative to larger mosquitoes. Midguts from small 'Starve' and large 'Control' Ae. aegypti were dissected to visualize by transmission electron microscopy (TEM) the midgut basal lamina (BL) as physical evidence for the midgut escape barrier showing Starve mosquitoes with a significantly thinner midgut BL than Control mosquitoes at two timepoints. ZIKV replication was inhibited in Starve mosquitoes following intrathoracic injection of virus, however, Starve mosquitoes exhibited a significantly higher midgut escape and population dissemination rate at 9 days post-infection (dpi) via blood-meal, with more virus present in saliva and head tissue than Control by 10 dpi and 14 dpi, respectively. These results indicate that Ae. aegypti developing under stressful conditions potentially exhibit higher midgut infection and dissemination rates for ZIKV as adults, Thus, variation in food intake as larvae is potentially a source for variable vector competence levels of the emerged adults for the virus.